Small boat navigating the White Horse Rapids on the Yukon River, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Shooting the White Horse Rapids" Original photograph by Eric A. Hegg 125A; copied by Adams and Larkin. Klondike Gold Rush